The Forms of Writing the Influential Iraqi Constitution - Badr Muhammed-Taher Mustafa; Abdulla Saeed Omer; Rekar Shams Aldeen (QALAAI ZANIST JOURNAL, 2022)
Without a doubt the subject of writing constitutions and issues that stand in the way are found quite important. For these new topics to study this further and to be addressed by specialists in the field of common law and constitutional law in particular. This is due to the sensitivity of topics related to the type of government and its philosophy and ways of exercising power and the statement of rights and freedoms to be protected and methods of protection, which guarantees the concept of good governance and administration. As for this perspective, the research will attempt to briefly and based on reliable sources set out the legal duties and interpretations that are to be considered when writing a constitution. A method of analysis of the issues facing the matter will be exercised. The political process in Iraq has suffered from various forms of deterioration, which has become largely the exercise of the political process in accordance with the due process of the rulers who are growing political power and the researchers will address the fundamental problem related to the obstacles that are the role of the political authorities that were accountable at the time which was represented by the coalition authority. The effectiveness of the political parties in drafting the provisions of the Constitution in accordance with the opinion and new aspirations and the role of civil society organizations and forces are also analysed throughout the thesis. The opposition in putting their ideas and objectives forward are found to be on board of the modern constitution and the accompanying conflicts of interests and orientations among the groups of Iraqi communities in all political, social, economic, cultural and sectarian aspects, which is undoubtedly one of the most difficult obstacles that faced the publication of constitutions and political history of Iraq attests to this and referred to it in the board of research and study and in the light of the above, this study came to discuss these issues and to further study the matter in order to understand it in the most relevant means.